Potential roles of the endoplasmic reticulum stress pathway in amyotrophic lateral sclerosis - Jeon, Yu-Mi; Kwon, Younghwi; Lee, Shinrye; Kim, Hyung-Jun (Frontiers in Aging Neuroscience, 2023)
The endoplasmic reticulum (ER) is a major organelle involved in protein quality control and cellular homeostasis. ER stress results from structural and functional dysfunction of the organelle, along with the accumulation of misfolded proteins and changes in calcium homeostasis, it leads to ER stress response pathway such as unfolded protein response (UPR). Neurons are particularly sensitive to the accumulation of misfolded proteins. Thus, the ER stress is involved in neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, prion disease and motor neuron disease (MND). Recently, the complex involvement of ER stress pathways has been demonstrated in experimental models of ALS/MND using pharmacological and genetic manipulation of the unfolded protein response (UPR), an adaptive response to ER stress. Here, we aim to provide recent evidence demonstrating that the ER stress pathway is an essential pathological mechanism of ALS. In addition, we also provide therapeutic strategies that can help treat diseases by targeting the ER stress pathway.